Does debt really crack the whip? Evidence from a Panel of Selected OECD Countries - Karagoz, Murat; Caglar, Mehmet (ELSEVIER SCIENCE BV, 2016)
External debt and GDP relationship has long been a focus of interest. The outcome of time series analyses and a few panel data outcome of previous studies are contradicting. In an attempt of unifying we have tried a panel data model of 17 selected OECD countries. We have estimated pooled regression, fixed effects and random effects models. The result in this first round of estimation was in favor of fixed and ultimately random effects model. However, error terms of all these models turned out to be serially correlated. To overcome this problem several alternative dynamic models have been experimented. Overall result of study shows that for the OECD countries the foreign debt growth relationships is a positive one. Although there are some countries in the world that have a negative relationship, for the case of OECD at least, positive relationships are indicative of good policy administration. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Foreign Debt; Growth Performance; Panel Data; Dynamic Models; GROWTH; Business & Economics